Professional courage to create a pathway within midwives' fields of work: a grounded theory study - Malin Hansson; Ingela Lundgren; Gunnel Hensing; Anna Dencker; Monica Eriksson; Ing-Marie Carlsson (BMC, 2021)
Abstract Background The theory of salutogenesis focuses on resources for health and health-promoting processes. In the context of midwives' work, this is not well described despite the importance for occupational health and the intention to remain in the profession. In order to promote a healthy workplace, it is necessary to consider the facilitating conditions that contribute to a sustainable working life. Therefore, the aim of this study was to explore health-promoting facilitative conditions in the work situation on labour wards according to midwives. Methods A constant comparative analysis was applied to face-to-face interviews with midwives that constituted the empirical material in this classical grounded theory study. Results The substantive theory of Professional courage to create a pathway within midwives' fields of work emerged as an explanation of the health-promoting facilitative conditions in midwives' work situation. The theory consists of a four-stage process with prerequisite contextual conditions: visualising midwifery, organisational resources and a reflective and learning environment, that were needed to fulfil the midwives' main concern a Feasibility of working as a midwife. This meant being able to work according to best-known midwifery theory and practice in each situation. Positive consequences of a fulfilled main concern were a professional identity and grounded knowledge that enabled the development of the resistant resource professional courage. The courage made it feasible for midwives to move freely on their pathway within the different fields of work extending between normal and medicalised birth and being autonomous and regulated. Conclusions A professional courage was required to create a pathway within midwives' fields of work, to move freely depending on what actions were needed in a particular work situation. Professional courage could be seen as a resistance resource, enabling midwives to become resilient when dealing with the unpredictable work situation. However, there are vital organisational preconditions that needed to be fulfilled for workplaces to become facilitative, organisational resources, visualising midwifery and a reflective environment. The theory can be used to foster health-promoting and sustainable work situations for midwives, which is possible if the organisational preconditions are met. This could be a key factor in retaining midwives in the profession.